Pengembangan Bahan Ajar Berbicara Berbasis Kesantunan Berbahasa (Development Of Speaking Teaching Materials Based On Language Politeness) - Akhyaruddin Akhyaruddin; Priyanto Priyanto; Ade Bayu Saputra; Arum Gati Ningsih; Andiopenta Purba; Nurfadilah Nurfadilah; Lusia Oktri Wini (Ranah: Jurnal Kajian Bahasa, 2024)
This research implements Leech and Grice's language politeness maxims in the development of Speaking teaching materials. The goal is to produce a product of Speaking Teaching Materials Based on Language Politeness. The method used to achieve this goal is Research and Development with the procedure of Analysis, Design, Development, Implementation, Evaluation. The method used to determine the feasibility of teaching material products developed is the questionnaire method of validation of language politeness material experts, teaching material readability experts, teaching material book graphics experts and teaching material user practitioners. The overall data obtained through the questionnaire is processed with descriptive statistics. Using Likert scale criteria, the results of expert validation show that the aspect of the material aspect of language politeness has a percentage of 88.66% with a very valid category, the graphical aspect of the teaching material book gets a percentage of 93.33% with a very valid category. The user practitioner test obtained the feasibility of teaching material products of 94.98% with a very feasible category. The results of the expert validation test and practitioner test show a percentage far above 61%. Thus, the product of Speaking Based on Language Politeness teaching materials produced is feasible to be implemented in the lecture process. AbstrakPenelitian ini mengimplementasikan maksim-maksim kesantunan berbahasa Leech dan Grice dalam pengembangan bahan ajar Berbicara. Tujuannya adalah untuk menghasilkan produk bahan ajar Berbicara Berbasis Kesantunan Berbahasa. Metode yang digunakan untuk mencapai tujuan tersebut adalah Research and Development dengan prosedur Analysis, Design, Development, Implementation, Evaluation. Metode untuk mengetahui kelayakan produk bahan ajar yang dikembangkan adalah metode angket validasi ahli materi kesantunan berbahasa, ahli keterbacaan bahan ajar, ahli grafika buku bahan ajar, dan praktisi pengguna bahan ajar. Keseluruhan data yang diperoleh melalui angket diolah dengan statistik deskriptif. Dengan menggunakan kriteria skala likert, hasil validasi ahli menunjukkan bahwa aspek materi kesantunan berbabahasa memilki persentase 88,66% dengan kategori sangat valid; aspek keterbacaan bahan ajar memeroleh persentase 97,33% dengan kategori sangat valid; aspek grafika buku bahan ajar memeroleh persentase 93,33% dengan kategori sangat valid.  Uji prktisi pengguna diperoleh kelayakan produk buku bahan ajar sebesar 94,98% dengan kategori sangat layak. Hasil uji validasi ahli dan uji praktisi tersebut menunjukkan persentase jauh di atas 61%. Dengan demikian, produk bahan ajar Berbicara Berbasis Kesantunan Berbahasa yang dihasilkan layak diimplementasikan dalam proses perkuliahan.